Impact of Industry 4.0 on labor productivity in the Slovak Republic - Adriana Grenčíková; Marcel Kordoš; Vladislav Berkovic (Problems and Perspectives in Management, 2020)
The Fourth Industrial Revolution bears major technological, demographic, and socio-economic changes affecting nearly every area in business. Within the human resources area, both a surplus of labor and the creation of brand new professions are to be expected. Industry 4.0 concept significantly affects labor productivity in individual countries and does not miss the Slovak Republic either. All segments of the labor market, not just industrial enterprises, will be affected. The present study aims to analyze the possible development of labor productivity in Slovak companies and determine its development in the next period, considering the decreasing number of working-age populations in terms of the fallouts on creation and termination of jobs and occupations. The questionnaire carried out in 319 enterprises in the Slovak Republic with a received response of 228 was a key research tool used to analyze the results of the survey. The findings show that although the labor force within the Slovak labor market will not increase, the labor force will decrease due to unfavorable demographic development. The overall productivity in Slovak companies will increase due to the new technologies implementation. The results have proved that the Industry 4.0 concept will significantly affect labor productivity in the world economy and the Slovak Republic. In particular, the recommendations aim to draw attention to changes in job structure and the need to reform the education system because of Industry 4.0 requirements. Acknowledgments This paper was supported by the Slovak Ministry of Education’s Scientific grant agency VEGA: “The impact of Industry 4.0 on jobs structure changes”. Project registration number: [Reg. No.: 1/0430/18]. This paper was supported by the Slovak Ministry of Education’s Scientific grant agency VEGA: “Assessment changes in the qualitative structure of international economic relations under the influence of Industry 4.0 with implications for the EU and Slovak economic policies”. Project registration number: [Reg. No.: 1/0462/20].